2016
DOI: 10.18410/jebmh/2016/264
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Renal and Urinary Tract Anomalies in Selected Neonates

Abstract: BACKGROUND Congenital anomaly of kidney and urinary tract (CAKUT) are among the most common anomalies diagnosed prenatally. Early diagnosis and timely intervention can preserve renal function and avoid morbidity. AIMS AND OBJECTIVES To screen, select at-risk newborns for congenital renal and urinary tract anomalies by postnatal ultrasound and to study the pattern of distribution, clinical presentation and its correlation with antenatal scan. MATERIALS AND METHODS It was a prospective study. Postnatal ultrasoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…20 Hydronephrosis accounted for the most common antenatally diagnosed CAKUT, seen in 28 out of 65 cases (43.1%) which was consistent with the fi ndings of various other similar studies. [18][19][20] Also the observation that abnormalities of the renal collecting system were more common than those of the renal parenchyma was similar to that of various other similar studies. 18,19 During our study we observed that antenatally, bilateral mild hydronephrosis was most common (53.6%).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…20 Hydronephrosis accounted for the most common antenatally diagnosed CAKUT, seen in 28 out of 65 cases (43.1%) which was consistent with the fi ndings of various other similar studies. [18][19][20] Also the observation that abnormalities of the renal collecting system were more common than those of the renal parenchyma was similar to that of various other similar studies. 18,19 During our study we observed that antenatally, bilateral mild hydronephrosis was most common (53.6%).…”
Section: Discussionsupporting
confidence: 87%
“…[18][19][20] Also the observation that abnormalities of the renal collecting system were more common than those of the renal parenchyma was similar to that of various other similar studies. 18,19 During our study we observed that antenatally, bilateral mild hydronephrosis was most common (53.6%). However in various other similar studies, it was observed that the left kidney was more often the site for hydronephrosis.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations